Methodic the Quantitative Assessment Factors the Inherent Risk of Audit - Mackevičius, Jonas; Valkauskas, Romualdas; Tamulevičienė, Daiva (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian] The purpose of this article is investigate factors the inherent risk and to create a methodic for quantifying the inherent audit risk. The article analyzes the inherent risk of audit essential features and its place in the overall audit risk system. It is shown that the inherent risk of audit is influenced by many factors, which can be divided into two groups: 1) the outside; 2) inside. All factors should be investigated early in the audit phase, in particular when developing an audit strategy and establishing an audit plan and programs. The assessment of these factors depends on the auditor’s competence. A quantitative assessment of the inherent risk of audit risk consisting four calculation steps: factors - indicator list formation; their assessment; determination of maximum assessment and determination the synthetic characteristics of the inherent audit risk and the determination of the level of risk. This methodology can be used in conjunction with other methods and models for audit risk assessment as a means of measuring as closely as possible the inherent audit risk and its determinants, and tracking its changes. Research methods: scientific literature analysis, grouping, comparing, detailing and aggregating information.